La biodiversité est-elle un enjeu pour les habitants ? - Laure Cormier; Fabienne Joliet; Nathalie Carcaud (Développement Durable et Territoires)
“Trame verte” has become trendy in the French planners’ vocabulary. It is to act on the materiality of the landscape, for example, by installing landscape structures for environmental purposes, or construction of infrastructure for recreation. These changes have a direct impact on ordinary landscape that, first of all, is living by inhabitant. But how this notion of “trame verte” is perceived by them? Thirty interviews with inhabitants of Angers’ agglomeration have been made. Interpretation of the results led to consider the appropriation of the term “trame verte” and the concept of biodiversity by residents and, more generally, expectations of “nature”.